Endoglin (CD105) and VEGF as potential angiogenic and dissemination markers for colorectal cancer - Nogués, Ana (World J Surg Oncol, 2020)
BACKGROUND: Colorectal cancer (CRC) is an important current problem concerning public health due to its high incidence and mortality. Advances in molecular and cellular knowledge and the detection of new disease biomarkers are very important to improve prognosis, prediction, and early diagnosis. In this study, we aimed to analyze the gene and protein expression levels of two angiogenic markers, VEGF and soluble Endoglin, during different tumor stages as well as at different stages of cancer treatment, to predict the diagnosis and evolution of colon and rectal cancer. MATERIAL AND METHODS: This study includes 133 CRC patients (93 with colon cancer and 40 with rectal cancer) on which the gene and protein expression of Endoglin (membrane and soluble form) and VEGF were analyzed by molecular and immunohistochemical techniques on different tumor stage samples and plasma obtained preoperatively as well as 3, 6, and 9 months after resection of the tumor. RESULTS: VEGF and Endoglin gene expressions were higher in tumor tissue than in surrounding non-tumoral tissue for both types of cancer. The VEGF levels in plasma were found to decrease in less aggressive tumors, whereas soluble Endoglin was increased in preoperative samples of patients with metastasis. Membrane Endoglin expression was higher on the vascular endothelium of more aggressive tumors. In contrast, Endoglin expression was mainly in the colon epithelium in less aggressive stage tumors. CONCLUSION: Endoglin and VEGF are proteins with a major role in the tumor angiogenesis process. This study performed with a wide cohort of human samples shows that both proteins seem to be valuable biomarkers in the diagnosis and prognosis of CRC.